Deiodinase 2 inhibition leading to increased mortality via reduced posterior swim bladder inflation - Vergauwen, Lucia (OECD Publishing, 2022)
This Adverse Outcome Pathway (AOP) describes the linkage between Deiodinase 2 inhibition and increased mortality via reduced posterior swim bladder inflation. The swim bladder is a gas-filled organ found in many bony fish species and typically consists of two gas-filled chambers. The posterior chamber inflates during early development (embryo), while the anterior chamber inflates during late development (larva). Both chambers are important for fish to control buoyancy and the anterior chamber has an additional role in hearing. This AOP is part of a network of 5 AOPs describing how disruption of the thyroid hormone system can affect developmental processes involved in swim bladder inflation. The network includes three molecular initiating events representing the inhibition of enzymes that are important for thyroid hormone synthesis and activation. It describes how inhibition of thyroperoxidase and/or deiodinase, leads to reduced swim bladder inflation, resulting in reduced swimming performance, increased mortality and ultimately, decreased population trajectory in fish. This AOP network is currently mainly based on experimental evidence from studies on fish species with a two-chambered swim bladder. This AOP is referred to as AOP 155 in the Collaborative Adverse Outcome Pathway Wiki (AOP-Wiki)
Keywords: Environment